2016
DOI: 10.1126/scitranslmed.aaf0685
|View full text |Cite
|
Sign up to set email alerts
|

The Human Vaccines Project: A roadmap for cancer vaccine development

Abstract: Cancer vaccine development has been vigorously pursued for 40 years. Immunity to tumor antigens can be elicited by most vaccines tested, but their clinical efficacy remains modest. We argue that a concerted international effort is necessary to understand the human antitumor immune response and achieve clinically effective cancer vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
111
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(112 citation statements)
references
References 70 publications
1
111
0
Order By: Relevance
“…However, as resistance to checkpoint blockade has become clinical reality and combination strategies are increasingly considered, there is a renewed interest in cancer vaccination (1,2). Cancer vaccines aim at inducing or restimulating tumor-specific T cell responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as resistance to checkpoint blockade has become clinical reality and combination strategies are increasingly considered, there is a renewed interest in cancer vaccination (1,2). Cancer vaccines aim at inducing or restimulating tumor-specific T cell responses.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer vaccines aim at inducing or restimulating tumor-specific T cell responses. Based on preclinical (1)(2)(3)(4)(5)(6)(7)(8)(9) and initial clinical reports (10)(11)(12), they could be instrumental in breaking primary resistance to checkpoint blockade of tumors with low mutational load (13)(14)(15) and in increasing response rates of highly mutated tumors, such as melanoma (11).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of cancer vaccination trials have only provided partial results in the induction of an efficient anti-tumor cytotoxic T lymphocyte (CTL) response, due to the poor immunogenicity of antigenic peptides when administered alone, 17 suggesting the need for more powerful vaccines also in combination with standard chemotherapy 18-20 or with immune checkpoint inhibitory antibodies. 21-23 We have recently reported that patients receiving dacarbazine (DTIC) one day before peptide (Melan-A and gp100)-vaccination plus interferon (IFN)-α show a progressive enhancement of the TCR repertoire diversity of Melan-A-specific CD8 + T cells, accompanied by the maintenance of highly-avid and beneficial anti-tumor activity, as compared with cells isolated from patients receiving vaccination alone.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite numerous studies, the efficacy of cancer vaccines remains inconclusive (55). Studies investigating neoantigens has prompted renewed excitement in the vaccine field (56).…”
Section: Pd-(l)1 Inhibitor Nonrespondersmentioning
confidence: 99%